Competence of Frontline Implementers in the Implementation of the Policy of Appointing State Treasury Officials to Work Units within the Ministry of Religious Affairs Office Ciamis Regency - Hidayat, Dasep Sanju; Muhafidin, Didin; Rusli, Budiman; Buchari, Rd. Ahmad (International Journal of Science and Society, 2024)
The new approach to state financial management began with the introduction of Law Number 17 of 2003 on State Finance, Law Number 1 of 2004 on State Treasury, and Law Number 15 of 2004 on the Audit of State Financial Management and Accountability. The implementation of Minister of Religious Affairs Regulation Number 32 of 2021, which essentially serves as a policy or program within the Ministry of Religious Affairs, outlines the procedures for appointing treasury officials. This process will significantly influence the transparency and accountability of budget management. The success of these policies in achieving their intended outcomes naturally depends on factors related to policy, organizational structure, and the surrounding environment. The competence of frontline implementers is the competence of policy implementers, while the competence of implementers is a work ability of each policy implementer which includes aspects of knowledge, skills, and work attitudes in accordance with the expected standardization. Minister of Religious Affairs Regulation Number 32 of 2021 Article 2 Paragraph 5 states that state treasury officials, namely Paying Warrant Signing Officers, Commitment Making Officials and Expenditure Treasurers must have a certificate of competence. With regard to the prerequisites to be able to carry out duties as a state treasury official, they must have competence, where one of the indicators of having this competence is eligibility indicated by the certificate obtained after following the certification process. To achieve good policy implementation cannot be achieved in a short time where there must be several stages taken. The first stage is called the fullness stage where it is very important to be qualified to be eligible for office, the next stage is quality, namely how the work is carried out better and who does it.